Analysis of Fuzzy Non-preemptive Priority Queuing Model with Unequal Service Rate - et. al., K. Selvakumari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article provides an effective method to analyze the performance measures of non-preemptive fuzzy priority queues with unequal service rates. Here the arrival rate and the service rate are in fuzzy numbers. Using a new ranking method, the fuzzy values are reduced to the crisp values. For that cause, both the Triangular Fuzzy Number (TFN) and Trapezoidal Fuzzy Number (TpFN) are chosen to establish the proposal's effectiveness. An illustration is given to find the efficiency of the performance measures of the fuzzy queuing model.